Analisis Kinerja Organisasi Seksi Pendapatan Lain-Lain Dinas Pendapatan Pengelolaan Keuangan dan Aset Daerah Kabupaten Pemalang (Studi Pelaksanaan Pengalihan Kebijakan PBB-P2) - Riska Rahmawati; Nina Widowati; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
In deal with the society demand of first-rate public service, it becomes an individual challenge to Other Income Section of Management Income of Finance and Region Asset Department (DPPKAD) District Pemalang in giving the service of land and building tax of rural and urban (PBB-P2). Through this research, the researcher wants to analysis the organization performance of other income section in associated with the existence of diversion PBB policy from central to region. The research phenomenon which is observed in this research is organization performance dimensions, which are dimension of productivity, dimension of orientation service quality of customer, dimension of responsivity, dimension of responsibility, and dimension of accountability. IIn based of the research that has been done, it can be known that the performance of other income section DPPKAD District Pemalang has not been optimal yet or good enough. This can be seen from some organization performance section that is still obstructed, including dimension of productivity, dimension of orientation service quality to customer, dimension of responsibility, and dimension of accountability. It is because the amount of workers is not appropriate with the work load that has to be accomplished. But it also there is no information board inside the service room that makes the organization lacks of giving the clarity to the society. The other dimension which is dimension of responsivity has got the good valuation. This aims to increase the performance of other income section in order to receive the new tasks that are related with diversion of PBB policy that can be more optimal and impacts on giving the first-rate service to society.